Biaryl Construction Based on Nickel-Catalyzed C–O Bond Activation - Diao, Haiyan; Shi, Zhangjie; Liu, Feng (Synlett, 2021)
Nickel-catalyzed carbon–oxygen bond activation is one of the most powerful strategies for the direct construction of various biaryl compounds. Under nickel catalysis, efficiently produced and naturally abundant arenol-based electrophiles can be activated and coupled with different aryl nucleophiles, including nucleophiles containing magnesium, zinc, boron, etc., to produce biaryl structural units. This Account summarizes recent progress on biaryl synthesis via nickel-catalyzed C–O bond activation.1 Introduction2 Coupling of Arenols and Arenol Derivatives with Aryl Magnesium Reagents3 Coupling of Arenols and Arenol Derivatives with Aryl Zinc Reagents4 Coupling of Arenols and Arenol Derivatives with Aryl Boron Reagents5 Others6 Conclusion
Keywords: C–O activation; nickel catalysis; C–C bond formation; biaryls; cross-coupling